Peran Lingkungan Madrasah dalam Meningkatkan Motivasi Belajar - Purwantoro, Farich; Nisa’, Khoirun (rogram Studi Pendidikan Guru Madrasah Ibtidaiyah (PGMI) Fakultas Tarbiyah dan Ilmu Keguruan Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH) Lamongan, 2023)
The objectives to be achieved in this research are: 1) To find out the role of the madrasah environment in increasing student learning motivation at Madrasah Ibtidaiyah Ihyaul Iman Renteng Gading Probolinggo. 2) to find out what factors support the role of the madrasa environment in increasing student learning motivation at Madrasah Ibtidaiyah Ihyaul Iman Renteng Gading Probolinggo. Methods This research uses qualitative research methods. The approach used in this study is a descriptive approach, which is an approach that describes a state of status of a phenomenon that occurs in words or sentences, then separated according to categories to become a conclusion. The place of this research is located at the Ihyaul Iman Renteng Gading Probolinggo Madrasah Ibtidaiyah Institute. Sources of data taken by researchers include; Primary Data and Secondary Data. While the data collection techniques in this study were obtained by observation, interviews and documentation. The data analysis technique in this study used descriptive analysis where the data obtained from the madrasa was presented in the form of a data description. Based on the results of research conducted by researchers that the role of the madrasah environment in increasing student learning motivation at Madrasah Ibtidaiyah Ihyaul Iman Renteng Gading Probolinggo plays a very important role. The madrasa environment also acts as an institution that can educate students' character and as a motivator for students. By providing motivation directly or indirectly students can have an orientation and be active in their learning. The madrasa environment is said to be able to play a role in increasing student learning motivation if there are supporting factors. The factors include; facilities and infrastructure, learning media and student learning resources. With this factor students will be motivated to always be active in learning.